The 5-minute herb and dietary supplement consult - Fugh-Berman, Adriane (5-minute consult (Series), 2003)
This unique book gives health care professionals a quick reference to herbs, minerals, vitamins, amino acids, probiotics, enzymes, over-the-counter hormones and other dietary supplements commonly used by consumers. The text covers claims, indications, scientific evidence, possible benefits, adverse effects, contraindications, and drug interactions.